Radical addition-polar termination cascade: efficient strategy for photoredox-neutral-catalysed cyclopropanation and Giese-type reactions of alkenyl N-methyliminodiacetyl boronates. Issue 13 (1st June 2020) - Liu, Yongjun; Luo, Wenping; Wu, Jiali; Fang, Yewen; Li, Yan; Jin, Xiaoping; Zhang, Li; Zhang, Zongyong; Xu, Fenfen; Du, Chan
Abstract : Silicate meets boronate: efficient cyclopropanation and Giese-type reactions of alkenyl N -methyliminodiacetyl boronates with alkyl silicates have been realized via a photoredox-neutral-catalysed radical-polar crossover process. Abstract : With radical addition-polar termination (RAPT) cascade as the strategy, efficient cyclopropanation and Giese-type reactions of alkenyl N -methyliminodiacetyl boronates have been realized by means of photoredox catalysis. With chloro- or bromomethyl silicate as the methylene source, a variety of cyclopropyl MIDA boronates as air- and chromatographically stable solids were prepared via photoredox-catalysed cyclopropanation of α-MIDA-boryl styrenes, 2-propenyl-BMIDA, and ethenyl-BMIDA. Moreover, photocatalytic Giese-type reactions of alkyl radicals with α-MIDA-boryl styrenes were also developed. It is essential for the successful radical conjugate addition employing alkyl silicates as the radical precursor. These RAPT cascades are characterized by a redox-neutral and additive-free process.